Prevalence Detection of Human Intestinal Helminths in Aljmail City - Libya - Omar Ahmed Omar Amar; Miloud Omar Asarat (African Journal of Advanced Pure and Applied Sciences, 2024)
Qualitative detection of helminths in human faeces samples alongside patient questionnaires has been used to study the prevalence of intestinal helminths in Aljmail area. Among of the 66 samples that were examined (i.e. 66 patients), we found 23(34.8%) patients were infested with helminths- Enterobius vermicularis helminths which was more prevalence 22(33.3%) than Strongyloides stercoralis worm infestation 01(1.5%). These infestations have been associated with other parasitic infections including Entamoeba histolytica 2(3.0%), and Giardia lamblia 7(10.6%). Regarding gender, infected males with helminths were 4(6.1%) while infected females were 19(28.8%). Intestinal helminths infestation is associated with various patients complaints, such as 17(25.7%) abdominal pain, 4(6.1%) nausea, 12(18.2%) frequent vomiting, 12(18.2%) flatulence and diarrhoea, 18(27.3%) loss appetite, 15(22.7%) anaemia, and 17(25.7 %) anal itching. We found that the prevalence of worm infestation was correlated to patients poor hygiene as 14(21.2%) had long nails, 8(12.2%) had family members infected with worms and 19(28.8%) had primary or lower educational levels. It is required to examine persons with worm infection, prescribe suitable medicine, health attention, and individual hygiene to minimize and prevent helminths infection.